PENGARUH PENAMBAHAN CANGKANG PENSI SEBAGAI CAMPURAN SEMEN TERHADAP KUAT TEKAN BETON Fc’ 14,53 Mpa - Syamsul Arif; Helga Yermadona; Masril Masril (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Pensi shell is a material that can be used as a substitute for fine agregat. Pensi shell has the potential to increase the strength of concrete and improve the properties of concrete. For this reason, the author is interested in conducting research using the Pensi Shell. This research was conducted at the Laboratory of Muhammadiyah University, West Sumatra, Bukittinggi City. This research is guided by the Indonesian National Standard regarding the manufacture of normal concrete and testing of the compressive strength of concrete, and the practical guidelines for Concrete Civil Engineering Study Program, Muhammadiyah University, West Sumatra. in this study the pensi shells were 0%, 3%, 5%, and 7Further testing of the results of testing the compressive strength of concrete we can see the comparison of whether normal concrete or concrete after we observe the concrete with the addition of the pensi shell as a mixture of cement to the compressive strength of the concrete, the increase in concrete increases the age of the concrete to 28 days, the compressive strength we are looking for is from the 3% percentage of 16.99 MPa, then the 5% mixture compressive strength of 11.89 MPa, and 7% of 14.15 MPa, and vice versa at the age of 24 days the concrete decreased. Keywords: Pensi Shell, Concrete, Concrete Compressive Strength Fc' 14.53 Mpa.